Investigation of Abrasive water jet machining parameters of Bismaleimide composites. Issue 14 (26th October 2022) - Iyer, N Prasanaa; Arunkumar, N.
ABSTRACT: Bismaleimide-based hybrid fiber composites (BMI) with their expanded thermomechanical properties have been broadly utilized in Aircraft primary applications. The supplanting of carbon fiber with other fiber (kevlar/glass/basalt) is redone to the requirements of the business. To maintain the surface quality, the hybrid composites can be machined with unconventional methods like Abrasive Water jet Machining. In this work, the exploratory examination of interaction boundaries, such as Water pressure (Wp ), Transverse speed (Ts ), Standoff distance (SOD), Abrasive mass flow rate (ma ) of AWJM on hybrid BMI composites was done. Experiments were conducted based on Design of Experiments created from Response surface strategy utilizing Central Composite Design (CCD) and the impact of interaction boundaries on kerf taper and surface roughness were analyzed. The experimental outcomes showed that for the minimum kerf angle, the significant parameters were transverse speed, water pressure, and abrasive flow rate and for minimum surface roughness, transverse speed was the significant parameter. The microstructure analysis revealed that plowing deformation of fiber and abrasive particle embedment at high speed and mass flow rate led to delamination of fiber, which was limited by optimal parameters essentially diminishing kerf taper and surface roughness.